Effect of fullerene acceptor on the performance of solar cells based on PffBT4T-2OD - Yiwei Zhang (2018)
We have studied bulk-heterojunction (BHJ) solar cells composed of the polymer PffBT4T-2OD as electron donor and three different electron accepting fullerenes, namely PC71BM, PC61BM and indene-C-60-bis-adduct (ICBA) in order to understand the impact of different fullerenes on the morphology and efficiency of the corresponding photovoltaic devices. Despite PffBT4T-2OD:ICBA devices being characterised by higher values of V-oc, they display the lowest power conversion efficiency (PCE) due to their lower J(sc) and FF values. We find that although all blend films have similar morphologies, X-ray scattering indicates a reduced degree of order within the fullerene domains in the ICBA-based film. Due to the high LUMO level of ICBA, the corresponding blends are characterised by a lower initial exciton dissociation and this associated with the reduced ordering within the ICBA domains results in increased geminate recombination of the photogenerated electrons in the fullerene-rich domains and a consequently reduced PCE of the corresponding devices.